Canadian Labour in Crisis: Reinventing the Workers' Movement - Lewchuk, Wayne (Labour / Le Travail, 2012)
The article reviews the book, "Canadian Labour in Crisis: Reinventing the Workers' Movement," by David Camfield.
Keywords: BOOKS – Reviews; CAMFIELD; David; CANADIAN Labour in Crisis: Reinventing the Workers' Movement (Book); Canada; Labor Unions; Nonfiction

Precarious Employment and Occupational Health and Safety in Ontario - Lewchuk, Wayne; Clarke, Marlea; De Wolff, Alice (Boom, Bust and Crisis: Labour, Corporate Power and Politics in Canada, 2012)
Examines how the increase in precarious employment has exacerbated health and safety hazards and injuries in Ontario work places. Concludes that the Canadian regulatory system is flawed. Based on surveys and interviews conducted in southern Ontario in 2005 and 2006.
Keywords: Business and politics; Economic conditions; Employee rights; Industrial relations; Labor policy